Environmentally-assisted grain boundary attack as a mechanism of embrittlement in a nickel-based superalloy. (March 2017) - Németh, A.A.N.; Crudden, D.J.; Armstrong, D.E.J.; Collins, D.M.; Li, K.; Wilkinson, A.J.; Grovenor, C.R.M.; Reed, R.C.
Abstract: The loss of ductility in the high strength polycrystalline superalloy 720Li is studied in air between room temperature and 1000 °C. Tensile ductility is influenced profoundly by the environment, leading to a pronounced minimum at 750 °C. A relationship between tensile ductility and oxidation kinetics is identified. The physical factors responsible for the ductility dip are established using energy-dispersive X-ray spectroscopy, nanoscale secondary ion mass spectrometry and the analysis of electron backscatter diffraction patterns. Embrittlement results from internal intergranular oxidation along the γ -grain boundaries, and in particular, at incoherent interfaces of the primary γ ′ precipitates with the matrix phase. These fail under local microstresses arising from the accumulation of dislocations during slip-assisted grain boundary sliding. Above 850 °C, ductility is restored because the accumulation of dislocations at grain boundaries is no longer prevalent. Graphical abstract: Image 1